The Influence Of Anti-Fraud Awareness, Organizational Culture And Whistleblowing System On Prevention At PTPN Lll (Persero) Medan City - Nia Azania Khairani; M. Irsan Nasution; Wan Fachruddin (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the influence of anti-fraud awareness, organizational culture, and the whistleblowing system on fraud prevention. Fraud is a serious problem that can cause financial and non-financial losses to organizations, thus requiring comprehensive and sustainable prevention efforts. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to respondents selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression to test the influence of each independent variable on the dependent variable. The results show that anti-fraud awareness, organizational culture, and the whistleblowing system partially and simultaneously have a positive and significant effect on fraud prevention. These findings indicate that increasing individual understanding of anti-fraud, strengthening organizational values ​​and norms, and implementing an effective whistleblowing system can strengthen fraud prevention efforts. This study provides a practical contribution to organizations in formulating more effective internal control policies and fraud prevention strategies.